2022
DOI: 10.3390/electronics11101572
|View full text |Cite
|
Sign up to set email alerts
|

Global Maximum Power Point Tracking of Photovoltaic Module Arrays Based on Improved Artificial Bee Colony Algorithm

Abstract: In this paper, an improved artificial bee colony (I-ABC) algorithm for the maximum power point tracking (MPPT) of a photovoltaic module array (PVMA) is presented. Even though the P-V output characteristic curve with multi-peak was generated due to any damages or shading discovered on the PVMA, the I-ABC algorithm could get rid of stuck on tracking the local maximum power point (LMPP), but quickly and stably track the global maximum power point (GMPP), thereby improving the power generation efficiency. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The initial attractiveness at r=0$$ r=0 $$ is denoted by β0$$ {\beta}_0 $$. For any pair of fireflies i$$ i $$ and j$$ j $$, located at xi$$ {x}_i $$ and xj$$ {x}_j $$, respectively, the Euclidean distance is described by Equation () 59 rijgoodbreak=‖‖Xigoodbreak−Xjgoodbreak=k=1dxi,kxj,k2.$$ {r}_{ij}=\left\Vert {X}_i-{X}_j\right\Vert =\sqrt{\sum \limits_{k=1}^d{\left({x}_{i,k}-{x}_{j,k}\right)}^2}.…”
Section: Methodsmentioning
confidence: 99%
“…The initial attractiveness at r=0$$ r=0 $$ is denoted by β0$$ {\beta}_0 $$. For any pair of fireflies i$$ i $$ and j$$ j $$, located at xi$$ {x}_i $$ and xj$$ {x}_j $$, respectively, the Euclidean distance is described by Equation () 59 rijgoodbreak=‖‖Xigoodbreak−Xjgoodbreak=k=1dxi,kxj,k2.$$ {r}_{ij}=\left\Vert {X}_i-{X}_j\right\Vert =\sqrt{\sum \limits_{k=1}^d{\left({x}_{i,k}-{x}_{j,k}\right)}^2}.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the reasons given above for enhancing the performance of a photovoltaic power generation system and realizing better efficiency in energy conversion, the IIBA was proposed in this paper, which was applied in MPPT when multiple peak values occurred in P-V curves with a PVMA under partial shading, so the GMPP could be tracked swiftly and, in turn, provide better performance in steady and dynamic responses compared to the conventional BA. In [24] the author first searched for the maximum power point (MPP) using the intelligent bee colony algorithm. Then, using traditional P&O algorithms, the next tracking direction was validated to track the global maximum point.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the maximum power point tracking technologies are unable to track the GP during PS conditions. Firefly [3,4], flower pollination [5], particle swarm optimization (PSO) [6,7], improved PSO [8,9], ant colony [10,11], Cuckoo search [12], the sensor-less artificial vision algorithm [13], the improved rat swarm optimizer algorithm [14], and whale optimization [15] are all bioinspired soft computing/optimization algorithms that are used to locate the GP. Although the GP moves in space and time as the shading pattern (SP) varies, research has confirmed that optimization approaches could generally follow it [16].These optimization algorithms have proven to be efficient in tracking the MPP during normal circumstances, but during PS, the process becomes complex, as it involves many iterations and is not suitable for dynamic environments individually.…”
Section: Introductionmentioning
confidence: 99%